CAPACITY OF SUNTER C RIVER IN NORTH JAKARTA - Mohammad Imamuddin; Muhammad Lutfi Fadilah (International Journal of Civil Engineering and Infrastructure, 2021)
Sunter C river is located on Yos Sudarso street at coordinates 6°8'32,63" South Latitude, 106°53'25,78" East Longitude and downstream Sunter C river is located on Sunter Barat river street coordinates 6°8'24,78" South Latitude, 106°51'24.68" East Longitude. In area around the Sunter C river, there are still frequent floods every time the rainy season arrives because of the narrowing of canal section in upstream area of Sunter C river and Sunter C river water can’t flow gravitationally to Sentiong river because the base elevation of Sentiong river is higher than Sunter C river. From the above conditions, it’s necessary to analyze the problem of flooding in Sunter C river area to find out whether Sunter C river can still accommodate water discharge based on rainfall in the last 10 years and does the Sunter C river need normalization. Based on the results of manual calculations and HEC-RAS application, the Sunter C river can’t accommodate water discharge based on rainfall for the last 10 years of 15.88 m3/s. At point 0 - point 3 it is necessary to normalize by widening the cross-section from 3.6 m to 8 m and at point 4 from 4.8 m to 8 m.